Data-driven Modelling and Optimized Management of the District Cooling System and Thermal Energy Storage in Gothenburg - Zabian, Omar Marwan Rafiq; Chan, Chi Tat (My University, 2022)
District cooling system (DCS) is a sustainable and cost-effective way to provide cooling energy in urban areas[1]. DCS is growing in Sweden due to the increase in cooling energy demand. In Gothenburg, an expansion of DCS will be done by installing more cooling units and a cold-water thermal energy storage unit (TES). This paper first models the potential operation of the TES of low loading temperature below 4 °C by using computational fluid dynamics model Ansys Fluent. Then, it formulates an investment model by using linear programming (LP) to investigate the optimal size of the units, potential benefits and drawbacks to the system, in 2040. The research results in this study demonstrate that the operation of discharging temperature of water of 1 °C is unlikely in the operational point of view due to the intensive mixing in the low-temperature zone. The thermocline layer is only established between the warm return water zone and the cold zone. The thickness of the thermocline layer grows with time with the conduction and diffusion due to temperature difference within the medium. The balance between the investment and the operational cost decides the optimum size for the TES and the new production plant. TES has an investment priority advantage as it has a cheaper investment cost compared with the use of mechanical chillers, and a lower operational cost because it can be charged during the off-peak hours with low electricity prices. However, one of the limiting factors for the size of TES is the available chiller’s capacity for charging the TES, and another factor is the peak cooling demand. TES is optimized with the lowest total cost by running on a daily cycle. It saves operational costs by charging during off-peak hours and discharging during peak hours. In addition, the absorption chiller is a cost-effective choice to invest in to charge the TES over the compressor chillers. This is due to the availability of free waste heat, which has given an operational cost advantage for the absorption chillers, even though they have higher investment costs. The optimal size of the investment of cooling units has some uncertainties due to the unavailability of assured data on the electricity price and cooling demand, which greatly affect the operation of the overall DCS in the future.
Keywords: Cooling Thermal Energy Storage, District Cooling Network, CFD, cost optimization v